(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The scientific theoretical foundations of the development of children’s sports in the Republic, the main directions in the works and speeches of the president, the national program of training personnel in presidential decisions and decrees on this field, the program of healthy generation, the physical education and sports programs, the law and other documents showed vividly.